2009
DOI: 10.1186/1471-2164-10-65
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and expression analysis of porcine microRNAs

Abstract: Background: MicroRNAs (miRNAs) are small ~22-nt regulatory RNAs that can silence target genes, by blocking their protein production or degrading the mRNAs. Pig is an important animal in the agriculture industry because of its utility in the meat production. Besides, pig has tremendous biomedical importance as a model organism because of its closer proximity to humans than the mouse model. Several hundreds of miRNAs have been identified from mammals, humans, mice and rats, but little is known about the miRNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 64 publications
3
78
1
Order By: Relevance
“…The lack of correlation between sequencing and northern blot results for miR396 expression in stressed J. pentantha could not be attributed to the source of RNA as same RNA samples were used for sequencing and Northern blot analysis. This lack of correlation between sequencing-based profiling and Northern profiling may largely be attributed to the biased-ligation with the adapters (Reddy et al 2009) or sequencing problems. Although miR393 was not found as differentially regulated by drought as per our cut off criterion, the small RNA blot analysis revealed its induction by drought in J. pentantha but not in I. campanulata (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of correlation between sequencing and northern blot results for miR396 expression in stressed J. pentantha could not be attributed to the source of RNA as same RNA samples were used for sequencing and Northern blot analysis. This lack of correlation between sequencing-based profiling and Northern profiling may largely be attributed to the biased-ligation with the adapters (Reddy et al 2009) or sequencing problems. Although miR393 was not found as differentially regulated by drought as per our cut off criterion, the small RNA blot analysis revealed its induction by drought in J. pentantha but not in I. campanulata (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, very few miRNAs have been shown to play important roles in HSC development in vertebrates in vivo. miR-142-3p is specifically expressed in HSCs (AGM and CHT) and T cells (thymus) in zebrafish, mouse and other species [15][16][17][18][19][20][21]. By knockdown of miR-142a-3p using 2 specific MOs, the numbers of HSCs and T cells were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-144 and miR-451, as direct targets of the critical hematopoietic master regulator GATA1, are required for erythropoiesis in zebrafish and mouse [11][12][13]. miR-142-3p is an evolutionally conserved miRNA of vertebrates, which is expressed in many different hematopoietic cells [14][15][16][17][18][19][20][21]. Chen et al [15] first reported that miR-142 is expressed in embryonic and adult hematopoietic tissues, including the fetal liver, bone marrow, spleen and thymus, in mice, indicating its role in both embryonic and adult hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our result suggested that ame-mir-2-1 and -13 are co-expressed and have the same function in the honeybee brain. The nucleotide lengths of ame-mir-2-1, -8, -13a, -34, -276, and -1000 were 1 to 2 nt shorter or longer at the 3 region than those of the registered sequences, which is often observed among various microRNA (Obernosterer et al, 2006;Long and Chen, 2009;Reddy et al, 2009). There are at least two possible explanations; one is that microRNA size actually varies in vivo, and the other is that either the microRNAs registered in the miRBase or isolated in our study represent partly degraded products.…”
Section: Cloning Of Micrornas From the Honeybee Brainmentioning
confidence: 87%